Rosmersholm - Macmillan, Duncan (Oberon modern plays., 2019)
Rosmersholm is positioned against the backdrop of a looming election, an atmosphere of uncertainty and a bloodthirsty press. In the grand house of an influential dynasty, John Rosmer holds the future in his hands. As he wanders the line between idealism and a painful past, he finds himself ever more torn.